Do Medical Homes Improve Quality of Care for Persons with Multiple Chronic Conditions?. (7th August 2018) - Swietek, Karen E.; Domino, Marisa Elena; Beadles, Christopher; Ellis, Alan R.; Farley, Joel F.; Grove, Lexie R.; Jackson, Carlos; DuBard, C. Annette
Abstract : Objective: To examine the association between medical home enrollment and receipt of recommended care for Medicaid beneficiaries with multiple chronic conditions (MCC). Data Sources/Study Setting: Secondary claims data from fiscal years 2008–2010. The sample included nonelderly Medicaid beneficiaries with at least two of eight target conditions (asthma, chronic obstructive pulmonary disease, diabetes, hypertension, hyperlipidemia, seizure disorder, major depressive disorder, and schizophrenia). Study Design: We used linear probability models with person‐ and year‐level fixed effects to examine the association between patient‐centered medical home (PCMH) enrollment and nine disease‐specific quality‐of‐care metrics, controlling for selection bias and time‐invariant differences between enrollees. Data Collection Methods: This study uses a dataset that links Medicaid claims with other administrative data sources. Principal Findings: Patient‐centered medical home enrollment was associated with an increased likelihood of receiving eight recommended mental and physical health services, including A1C testing for persons with diabetes, lipid profiles for persons with diabetes and/or hyperlipidemia, and psychotherapy for persons with major depression and persons with schizophrenia. PCMH enrollment was associated with overuse of short‐acting β ‐agonists among beneficiaries with asthma. Conclusions: The PCMH model can improve quality of care for patients with multiple chronic conditions.